A complicated case of cutaneous necrotizing vasculitis associated with monoclonal gammopathy. Case report - Irina G. Rekhtina; Olga A. Vorobyeva; Elisavetta A. Atroshenko; Alla M. Kovrigina; Larisa P. Mendeleeva (Терапевтический архив)
Diagnosing diseases related to monoclonal gammopathy (MG) with clinical significance is challenging. In real-world practice, proving the connection between organ damage and paraprotein or plasma cell dyscrasia is difficult or even impossible. Only an atypical course of the disease and non-compliance with the established criteria may suggest the contribution of plasma cell neoplasia in pathogenesis. Rheumatic diseases associated with monoclonal secretion do not belong to MG with clinical significance. Therefore, in the absence of hematological malignancy, clone reduction therapy is not indicated. We present the first clinical case of a patient with cutaneous necrotizing vasculitis and MG, who received clone reduction therapy with no hematological malignancy. The rationale for the choice of such treatment approach was the atypical course of vasculitis, as well as the unstable effect after methylprednisolone therapy. Therapy with lenalidomide, cyclophosphamide, and dexamethasone was highly effective; the regression of clinical symptoms was associated with a decrease in paraprotein to trace amounts. However, the lack of evidence of the relationship of vasculitis with plasma cell dyscrasia does not support considering the described case as one of the forms of MG with clinical significance. Further observation and resumption of monoclonal secretion, coinciding with the recurrence of vasculitis, may additionally support the relationship between these two conditions. This case was discussed at the Council of Experts with hematologists, rheumatologists, and pathologists.